FRI0143 THE EFFICACY AND COST-EFFECTIVENESS OF HYDROXYCHLOROQUINE, SULFASALAZINE, METHOTREXATE TRIPLE THERAPY IN PREVENTING RELAPSE OF RHEUMATOID ARTHRITIS. (2nd June 2020) - Zhao, J.; Zhou, W.; Wu, Y.; Ji, P.; Yan, X.; Yang, L.; Zhang, Z.
Abstract : Background: TNFα inhibitors (TNFi) is effective for rheumatoid arthritis (RA) patients refractory to conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), but because of high cost, the discontinuation is common that often lead to disease relapse. Objectives: To investigate, among RA patients refractory to csDMARDs but achieved therapy target after treated with TNFi and methotrexate (MTX), if the combination therapy of csDMARDs is more effective in reducing disease relapse than MTX monotherapy, and more cost-effective than continuing the treatment with TNFi and MTX. Methods: In this multi-center, outcome assessment blinded, randomized, superiority clinical trial, RA patients who failed to csDMARDs treatment (DAS28(CRP)>3.2) received MTX plus TNFi for 12 weeks first (induction therapy). Then patients achieving low disease activity [LDA, DAS28(CRP)<3.2] were randomized into three groups in 1:1:1 ratio: (A) maintaining TNFi + MTX for 60 weeks; (B) adding hydroxychloroquine (HCQ) and sulfasalazine (SSZ) for 12 weeks and then removing TNFi but continuing HCQ and SSZ for 48 weeks; and (C) maintaining TNFi + MTX for 12 weeks and then removing TNFi but continuing MTX only for 48 weeks. The primary outcome is disease relapse [DAS28(CRP) increased by at least 0.6 and >3.2] in 60 weeks. Secondary outcomes include the incremental cost effectiveness ratio (incremental cost per reducing 1% relapse rate); adverse events and radiology progression. Results: 117 patients were enrolled for induction therapy. 67 patients achieved LDA after 12 weeks of induction therapy and were randomized with 21, 24 and 22 patients into each group, respectively. Male [OR=0.046 (0.005-0.451), p=0.008] and less baseline tender joint count [OR=0.825 (0.710-0.958), p=0.012] were independent predictive factors for LDA achievement. The relapse rate in 60 weeks was comparable between group A and B [33.3% (7/21) vs. 37.5% (9/24), p>0.05], while both significantly lower than that of group C [77.3% (17/22), p<0.01, p<0.01, respectively]. The adverse events and modified Sharp score progression were both comparable among the three groups. The incremental cost effectiveness ratio of group A is higher than group B (1315.7 yuan vs 101.5 yuan). Conclusion: For RA patients refractory to csDMARDs but achieved therapy target after treated with TNFi and MTX, the triple therapy of MTX+HCQ+SSZ is as effective as and more cost-effective than TNFi maintain therapy in reducing disease relapse. Both strategies are more effective than MTX monotherapy. References: [1]Smolen JS, Landewé R, Bijlsma J, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease- modifying antirheumatic drugs: 2016 update.Ann Rheum Dis. 2017 Jun; 76(6):960-977. [2]Smolen JS, Nash P, Durez P, et al. Maintenance, reduction, or withdrawal of etanercept after treatment with etanercept and methotrexate in patients with moderate rheumatoid arthritis (PRESERVE): a randomized controlled trial. Lancet. 2013;381(9870):918-29. [3]Rantalaiho V, Sandström T, Koski J, et al. Early Targeted Combination Treatment with csDMARDs Sustains Excellent Long-term Outcomes in Rheumatoid Arthritis. Arthritis Care Res (Hoboken). 2018 Oct 8. [4]Henaux S, Ruyssen-Witrand A, Cantagrel A, et al. Risk of losing remission, low disease activity or radiographic progression in case of bDMARD discontinuation or tapering in rheumatoid arthritis: systematic analysis of the literature and meta- analysis. Ann Rheum Dis 2018;777:515-22. Disclosure of Interests: None declared